A arbitragem sob a perspectiva econômica do direito: uma alternativa para a democratização do acesso à justiça nas relações empresariais - Dias, Feliciano Alcides (Universidade do Vale do Rio dos Sinos, 2017)
Changes to the hypermodern society and the organization of companies have caused the expansion of new decision-making processes through cooperated means of treatment and settlement of litigations, which started to be used more frequently by interested parties in addition to the jurisdictional services by the State. From this point of view, arbitration may be regarded as a democratic development tool for access the justice, as it emphasizes the agent´s condition to settle conflicts of private and financial nature, in view that it is grounded on the principle of autonomy of will of the parties. Incredulity of a great part of the Brazilian society to settle its conflicts through the local Judiciary Power results from its inefficiency, delay and unpredictableness when providing its services to population, which may have negative reflections on the economic development of Brazil. As a result, it must be examined if arbitration is an efficient mechanism as an economic institution in view of the reasons for which individuals and companies decide to settle their conflicts by including arbitration clauses in their agreements having the possible reduction in the transaction costs. Therefore, the new arbitration legislation aims at emphasizing the guarantee of democracy expressed by participation of the parties in the process conduction, which is consolidated through constitutional definition of the Brazilian civil procedure law. Such a situation stresses the interpretation of the phenomenon presented under matrix of the hermeneutical, phenomenological method and approach of the Law Economic Analysis associated to conduction of an empirical investigation of exploratory and field nature of the main Chambers of Arbitration in the State of Santa Catarina. Arbitration is a fast, reliable mean of litigation settlement inserted in an extrajudicial contributive dimension in the legal, social, and economic area.
Keywords: Acesso à justiça; Arbitragem; Análise econômica do direito; Custos de transação; Access to justice; Arbitration; Law economic analysis; Transaction costs; ACCNPQ::Ciências Sociais Aplicadas::Direito